Design evolution and knowledge handling for product conceptualization in new product development - Rao, Zhiming (2008)
The highly competitive and rapidly changing global business environment requires companies to deliver new products with better performance, lower cost, higher quality and shorter time-to-market. To develop a successful product, conceptualization of the product plays an extremely important role and, hence, deserves much more attention. In essence, this work views product concept development (PCD) as a strategic task that has a major impact on subsequent production related activities. In PCD, design evolution and evaluation are of great importance to generate satisfactory design concepts. To facilitate the efficiency of PCD and, hence, shorten the time-to-market, this work aims at establishing new approaches and methodologies to address the decisive issues of design evolution and evaluation in product conceptualization. In so doing, it is found that current practices and literature have not adequately addressed the issue of design information reuse in conceptual design evolution. Such difficulties as indexing, retrieval and modification of prior design knowledge remain to be dealt with. On the other hand, a knowledge-based approach has been recognized as a promising and logical alternative to support design evaluation. However, it is well-known that knowledge acquisition is the most time-consuming phase, and, therefore, the bottleneck in constructing a knowledge-based system (KBS). There are two major omissions in existing work. First, the quantitative characteristics of information and interrelationships between various knowledge elements, which are of critical importance in constructing a KBS, have not been investigated. Second, an integrated and easy-to-use knowledge acquisition process with a well-organized knowledge representation scheme to facilitate rule generation needs to be explored. Accordingly, a feature-based design evolution approach via case-based reasoning (CBR) is proposed to facilitate the evolution process of concept generation. In this approach, a feature relationship decomposition (FRD) procedure is postulated. The FRD provides an indexing scheme of CBR for design reuse with more flexibility of case retrieval. The performance of analytical hierarchy process (AHP) is enhanced with FRD via reducing the lengthy calculations of pair-wise comparisons. To arm the proposed design evolution approach with the capability of innovation, a TRIZ-enhanced innovative adaptation procedure (IAP) is investigated. Additionally, a matrix representation and mapping approach (MRM) is proposed to tackle the difficulty of knowledge acquisition in constructing a KBS to support design evaluation. The MRM approach establishes a systematic procedure to model the rule generation process mathematically. It uses matrix representation and mapping techniques to represent the knowledge attributes and reveal their interrelationships. It addresses the quantitative characteristics of relationship strength between various knowledge elements using a relationship estimation procedure. Three case studies on wood golf club design, hard disk design, and diagnosing automotive systems are employed to verify the proposed approaches, i.e. FRD, IAP, MRM, respectively. The economic impact of this work is to enhance design efficiency in new product development so as to reduce design time and hence cost by effectively making use of historical design data. In this work, the proposed CBR-based design system has been tested on tangible product design problems. Given the proposed benefits, the possibility of extending the current work to a broader scope will merit further exploration.